Disrupted water governance in the shadows: Revealing the role of hidden actors in the Upper Cauca River Basin in Colombia - Figueroa-Benitez, Alejandro; Nagheeby, Mohsen; Figueroa, Apolinar; Amezaga, Jaime (Frontiers in Water, 2023)
Colombia’s policy in the Upper Cauca River Basin is diminished by a lack of legitimacy in local areas respecting the control of territory and water. Such illegitimate interference provides a hiding place and fertile ground for the illegal activities of ‘hidden’ actors. The potential power of such hidden actors to influence water governance has not before been scrutinised in academic studies. We engage with critical discussions of governance to reveal the role of these actors in controlling territory and water in the Upper Cauca River Basin. This is supported by an analysis of recognition and representation processes and of the intricate socio-political conditions surrounding water management in this river basin. Extensive fieldwork was carried out, including workshops, interviews, and informal talks. Despite the Colombian government not recognising hidden actors and their part in influencing water-related policies, the information gathered revealed their active agency in the basin. These actors play a determining role in territorial development and water resource management, disrupting the functioning of the State’s water governance. Hidden actors, to promote their own, mostly illegal and illegitimate businesses, seize upon the current lack of clarity in the national normative standards, the deficiencies created by an inconsiderate implementation of national water policy, and the State’s lack of legitimacy at the local level. This paper contributes to critical literature on water governance and provides a better sense of the reality on the ground for policymakers in Colombia.